Psychometric Properties of the Saudi Version of the Mathematics Confidence Scale using the Modern Test Theory - Alnaimi, Izzeldeen Abdullah; Alenezi, Abdullah Khretan; Shindi, Yousef Abdelqader Abu; Al-Zboon, Habis Saad; Gaberkassem, Abd El. MureedAbd El (Journal of Ecohumanism, 2024)
The aim of the study was to analyze the psychometric properties of the Arabic version of the Math Confidence Rating Scale (MCS), using Item Response Theory (IRT) and Exploratory Factor Analysis (EFA). The participants were (315) from Imam Mouhammad Ibn Saud Islamic University; They are distributed into (92) female and (223) male, selected through a convenience sampling. The EFA models indicated that the one-dimensional structure better represents the data, and the pairs of items were considered locally independent, IRT findings indicate that all items had a very high discrimination parameter and all items had acceptable threshold parameters, And that MCS is more informative for mid-level ability of Math confidence. The MCS in Arabic has adequate psychometric properties to be used as a short measure of Math confidence.